PENGARUH DANA ALOKASI KHUSUS DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA MODAL PEMERINTAH KABUPATEN/KOTA DI SULAWESI TENGGARA TAHUN 2003-2017 - Rany Tri Septiani; La Ode Muh Harafah; La Ode Suriadi (Universitas Halu Oleo, 2017)
The research of this study to analyze the effect of Special Allocation Funds and Regional Original Revenues on Government Capital Expenditures in Southeast Sulawesi District / City. The type of data in this study is Secondary data. Data analysis techniques in this study are panel data regression analysis. The results in this study indicate that simultaneously and partially Special Allocation Funds and Regional Original Revenues have a significant effect on Capital Expenditure. Partially the effect of DAK the bigger compared with PAD.